VIII Workshop and Competition for young scientists in the field of statistical physics and condensed matter theory (Condensed Matter Physics, 2007)
Institute for Condensed Matter Physics of the National Academy of Sciences of Ukraine announces
an annual competition for young researchers working in the field of statistical physics and
condensed matter theory. The best works selected by the Competition Committee will be commended
by Special Individual Awards. The competition was established in 2001 and is dedicated to
the anniversary of the foundation of the first Institute department, the Department for Statistical
Theory of Condensed States (May, 1969).